2018
DOI: 10.1016/j.ceramint.2017.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical nano ZnO-micro TiO2 composites: High UV protection yield lowering photodegradation in sunscreens

Abstract: TiO 2 is a commonly used semiconductor photocatalyst but, as a paradox, it is also widely used as UV filter in sunscreens. Moreover, its capacity to form free radicals under UV irradiation generates reactive free radicals that provoke sunscreens degradation. In this work a hierarchical composite made of ZnO nanoparticles anchored onto TiO 2 microparticles is developed in a safe-by-design way by using the sol-gel method. The aim of this composite is to gain the advantages of inorganic nanoparticles avoiding the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 43 publications
0
53
0
2
Order By: Relevance
“…Another drawback of inorganic compounds as ZnO and TiO 2 is the generation of free radicals when exposed to UV radiation [4]. In this sense, encapsulation of inorganic nanoparticles becomes a promising technique to reduce the formation of free radicals when exposed to UV radiation, beyond the contribution to the translucent appearance of the Sunscreens [4,5]. Also, the encapsulation of organic compounds may improve photostability, photo protection and safety of the compounds [6].…”
Section: Introductionmentioning
confidence: 99%
“…Another drawback of inorganic compounds as ZnO and TiO 2 is the generation of free radicals when exposed to UV radiation [4]. In this sense, encapsulation of inorganic nanoparticles becomes a promising technique to reduce the formation of free radicals when exposed to UV radiation, beyond the contribution to the translucent appearance of the Sunscreens [4,5]. Also, the encapsulation of organic compounds may improve photostability, photo protection and safety of the compounds [6].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, understanding of the functionality-material relationships is likewise necessary in order to develop functional materials [22]. Depending on the materials properties to be exploited for a distinct application, it might not be possible to maximise both functionality and safety at the same time, as highlighted by Reinosa et al [7]. …”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that modification of fibers with inorganic particles (SiO 2 , ZnO and TiO 2 ) can affect the stability of PLA. ZnO and TiO 2 are effective absorbers of UV [24,25] and are commonly used as UV-screen agents in sunblocks. Zhang reported that ZnO nanoparticles can stabilize poly(butylene succinate-co-butylene adipate) matrix and hinder the photodegradation of polymer [26].…”
Section: Introductionmentioning
confidence: 99%